2014
DOI: 10.3390/nu6041649
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Homocysteine Increases Risk of Metabolic Syndrome in 6 to 8 Year Old Children in Rural Nepal

Abstract: Little attention has been given to the association of plasma homocysteine (Hcy) and metabolic syndrome (MetS) in children. We have evaluated the risk of MetS with plasma Hcy in a cohort of 6 to 8 year old rural Nepalese children, born to mothers who had participated in an antenatal micronutrient supplementation trial. We assessed Hcy in plasma from a random selection of n = 1000 children and determined the relationship of elevated Hcy (>12.0 μmol/L) to MetS (defined as the presence of any three of the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…This study also showed that HDL-C was lower in COPD + CVD patients. Hcy level was positively correlated with BMI, which was consistent with the reports of and Ikkruthi et al (2013) and Yakub et al (2014) Hcy is also associated with lipid metabolism. In a cohort survey based in Chinese population of a community, it showed that hyperhomocysteinemia was related to increasing risk of low HDL-C and high TG, it predicted that Hcy levels might influence lipid metabolism ( Momin et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…This study also showed that HDL-C was lower in COPD + CVD patients. Hcy level was positively correlated with BMI, which was consistent with the reports of and Ikkruthi et al (2013) and Yakub et al (2014) Hcy is also associated with lipid metabolism. In a cohort survey based in Chinese population of a community, it showed that hyperhomocysteinemia was related to increasing risk of low HDL-C and high TG, it predicted that Hcy levels might influence lipid metabolism ( Momin et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…HHcy has been proven in recent studies to promote the progression of metabolic syndrome [12,13] and type 2 diabetes [14], which are characterized by insulin resistance. However, it unclear whether HHcy portends the progression of insulin resistance diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia (HHcy), a pathological condition characterized by elevated total homocysteine (tHcy) concentrations (usually defined as tHcy concentrations > 15 μmol/L) in blood, is a well established risk factor for neural tube defects (NTDs), and it also has been associated with many non-communicable diseases (NCDs), including cardiovascular and cerebrovascular diseases, type 2 diabetes, and cancers [ 1 , 2 , 3 , 4 , 5 ]. In the past two decades, numerous studies have been conducted in developed countries to explore tHcy status and its determinants.…”
Section: Introductionmentioning
confidence: 99%